Examination of Periodontal Health Status in Sulfur Mustard Gas Intoxicated Warfare Veterans: A Cross-Sectional Study - Mahdi Balali-Mood; Majid Ghayour-Mobarhan; Atessa Pakfetrat; Javad Sarabadani; farzaneh mohamadzadeh mahrokh; Ali Labafchi (Mashhad University of Medical Sciences, 2022)
Introduction: A great number of Iranian military forces have sustained sulfur mustard gas exposure during the Iran-Iraq war of 1980-1988 and have survived with dental care needs. Accordingly, this study aimed to discover the prevalence of intraoral lesions and periodontal diseases associated with the percentage of being chemical veterans. Methods: This cross-sectional study was conducted in the summer of 2009 on 40 chemical veterans. The patients were examined using dental mirrors under dental unit light, as well as a periodontal probe, to evaluate soft tissue attachment. The clinical results were then documented on medical records. Data were analyzed using the Chi-square test and two independent sample t-tests in SPSS software (version 19). A p-value less than 0.05 was considered statistically significant. Results: The study population was composed of 40 patients with a mean age of 50.7±9.32 years, mean pocket depth of 1.47±0.31 mm, and mean bleeding on probing of 0.35±0.24 mm. Furthermore, 55% and 27.5% of the patients had xerostomia and temporomandibular joint dysfunction, respectively. However, no significant association was found between these factors and the percentage of being veterans. Conclusion: The study findings showed that 96.7% of the patients had bleeding on probing problem. The mean score of plaque index that is a practical measurement on evaluating oral hygiene was 2.06±0.99. Therefore, informing chemical veterans about their periodontal health by performing regular dental assessments by dental specialists and instructing oral hygiene seem to be this group's need.